KEKERASAN DAN STRUKTUR MIKRO BAJA AISI 1040 SEBAGAI HASIL PROSES QUENCHING MENGGUNAKAN PENDINGIN AIR GARAM DAN ASAP CAIR - Tafrant, Dodi; Hendradinata, Hendradinata; Mulyadi, Mulyadi; Sampurno, Rachmat Dwi; Sani, Almadora A.; Karmin, Karmin; Hidayat, Randy; Muzafar, M. Agil; Fitriani, Devita Dinda (MACHINERY Jurnal Teknologi Terapan, 2022)
Steel with various uses has an important role in machining and construction processes. In its use, steel is chosen because of its strength, ductility, and hardness. One type of steel commonly used in the machining process is AISI 1040 steel. This is because AISI 1040 steel has tough, strong, and hard properties. However, in its use sometimes AISI 1040 steel must be hardened to be more capable in its use. In that endeavor, AISI 1040 steel can be subjected to heat treatment to change its microstructure from initially Ferrite and Pearlite, to Martensite. This change in microstructure has an effect on increasing the hardness value of AISI 1040 steel. This study was conducted to determine how much effect the increase in hardness value would have if AISI 1040 steel was subjected quenching using brine and liquid smoke as cooling media. The results obtained were an increase in the hardness value of AISI 1040 steel to 63.76 HRc, and 65.40 HRc for each cooling medium. The visible microstructure is the formation of a martensitic phase on AISI 1040 steel after heat treatment.